2007
DOI: 10.1109/mwsym.2007.380453
|View full text |Cite
|
Sign up to set email alerts
|

24GHz Intruder Detection Radar with Beam-switched Area Coverage

Abstract: A 24GHz Intruder detection radar with three vertically-switched-beam antennas has been developed to cover a fan-shaped ground area with 90 degs. in azimuth and 0 to over 14m in range, when mounted at a height of 5m. Each switched beam monitors a different range segment with a monopulse scheme employed to achieve the wide azimuth coverage. An experimental radar with a Tx/Rx module fully assembled with MMIC's successfully detected a human intruder with a position accuracy of 50cm when moving at 1.4m/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 3 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Novel RF beamforming techniques are emerging for applications with higher frequencies. Researchers have designed complex delay lines and switch-antenna arrays to realize beam scanning for FMCW radar systems [ 57 , 58 , 68 ]. However, these methods usually have a limited number of steering angles.…”
Section: Recent Advancementsmentioning
confidence: 99%
“…Novel RF beamforming techniques are emerging for applications with higher frequencies. Researchers have designed complex delay lines and switch-antenna arrays to realize beam scanning for FMCW radar systems [ 57 , 58 , 68 ]. However, these methods usually have a limited number of steering angles.…”
Section: Recent Advancementsmentioning
confidence: 99%
“…Bellot Rubio, Ruiz Cobo & Collados (2000) suggested that the strong velocity gradients, if they exist, would be responsible for the asymmetries and zero-crossing shifts of the Stokes V profiles in plage regions at the disc centre. With Hinode high-resolution measurements of pores and their surrounding regions, Morinaga et al (2007) interpreted the Stokes V area asymmetry as being a systematic inflow of plasma into the magnetic concentrations from their surroundings. These above results support the idea that the turbulent convection of fluid is coupled with the magnetic flux tube on a small scale.…”
Section: Quantitative Analysis Of the Scanning Spectrum Averaged In Tmentioning
confidence: 99%